High‐Mobility Organic Light‐Emitting Semiconductors and Its Optoelectronic Devices. Issue 1 (13th October 2020) - Liu, Yanwei; Guo, Yunlong; Liu, Yunqi
Abstract : An organic light‐emitting transistor (OLET) integrates the field‐effect trans‐conductance characteristics of an organic field‐effect transistor (OFET) and the electric‐injection light‐emitting properties of an organic light‐emitting diode (OLED). The corresponding active layer of the device achieves controllable photoelectric coupling conversions. Therefore, a new method is theoretically provided for studying the carrier transmission characteristics and exciton emission theory. Furthermore, the integrated device characteristics of OLETs render their potential to advanced display technology, multifunctional optoelectronics, and electrically pumped organic lasers. However, OLET devices are yet to meet industrial requirements, mainly due to limitations in material performance and device fabrication techniques. Herein the basic factors that influence the mobility and luminescence properties of semiconducting materials are outlined and recent reports on OLET devices with a focus on material design, device fabrication, and operational mechanisms are summarized. More specifically, new functional optoelectronic devices based on high‐mobility emissive materials are described, including OFET–OLED active circuits based on the same active material, optical switching devices, and organic field‐effect optical waveguides. Herein, new insight into material design and device fabrication, which may be of great interest to scientists working in the field, is provided. Abstract : The basic factors that influence the mobility and luminescence properties are discussed herein. J‐aggregates with moderate exciton binding energy ( E B ) and mobility are advocated for the molecule design of high‐mobility emissive organic semiconductors. Subsequently, representative works of the organic light‐emitting transistor and the corresponding optoelectronic device are outlined.